Prevalence of Obstructive Sleep Apnea in Patients with Difficult Intubation: Looking for Evidence? - Eldin, Mohamed Shams; Yehia, Ayman; Abdallah, Randa; Shalaby, Gehan; Abdelaziz, Marwa (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: The link between obstructive sleep apnea and difficult intubation needs to be fully investigated and made clear. If a compromised airway can be anticipated and managed; it can lessen the likelihood of adverse consequences. AIM: The aim of this study was to investigate the incidence, severity, and possible association of obstructive sleep apnea in individuals with unexpected difficult endotracheal intubation and their associated clinical and polysomnographic findings. METHODS: Thirty patients referred for examination after difficult endotracheal intubation were enrolled in the study group, while 30 cases from the sleep laboratory unit database with a history of surgical intervention without difficult intubation were randomly selected for the control group. Documentation was obtained for the office clinical examination and fiber-optic nasopharyngolaryngoscopy assessment by Muller maneuver. The inspected upper airway was graded clinically using the Modified Mallampati technique. A comprehensive polysomnographic assessment was done overnight. The available data from the anesthetic record, as well as those derived from clinical and polysomnographic examination, such as age, sex, Body mass index, M Mallampati score, clinical positive findings, Cormack and Lehane grade, Apnea-Hypopnea Index (AHI), desaturation index, and average O2%, were statistically analyzed. RESULTS: The mean ± SD of the AHI of the study group was (29.7 ± 16.1) while in the control group, it was (13.1 ± 9.9), and the difference was of statistical significance (p < 0.001). The grading of the severity of obstructive sleep apnea (OSA) was significantly different between both groups, with 53.3% of the studied cases having severe OSA and the rest having moderate (26.7%) or mild OSA (13.3%). The desaturation index was significantly higher in the study group (28.9 ± 17.4) than the control group (10.2 ± 7.4), while the average O2% saturation was significantly lower among cases (91.8 ± 6.2). The mean modified Mallampati score was significantly higher among cases with grade III-CL, and the significance was also noticed in class IV. CONCLUSION: OSA is a major risk factor for difficult airway management and OSA patients are more likely to have difficult intubations. Patients who underwent a difficult intubation had a higher incidence and severity of OSA compared to the control group. OSA severity and higher modified Mallampati scores were independently related.